2009
DOI: 10.17741/bgsf/81.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transect of the Karelian Craton from margin to core based on P-T data from garnet and clinopyroxene xenocrysts in kimberlites

Abstract: Peridotitic garnet and clinopyroxene xenocrysts from the 1.2 Ga Lentiira-Kuhmo and the 760 Ma Kuusamo kimberlite fields, emplaced within the Central Karelian Craton, have been studied using major and trace element geochemistry to obtain information on the stratigraphy, compositional variability, and evolutionary history of the underlying lithospheric mantle. An earlier study on the 600 Ma Kaavi-Kuopio kimberlite field showed that near the SW margin of the craton the 230-km-thick subcontinental lithospheric man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This interpretation conforms with a number of other studies of the Baltic Shield (cf. Artemieva & Thybo 2008 for a recent review), including studies of xenoliths from Finland (Lehtonen et al 2004;Lehtonen & O'Brien 2009). The low P velocities and even lower S velocities and associated high V P /V S ratios west of the UMVB are consistent with a relatively thin, and hence warmer and less depleted lithosphere and a clear asthenosphere low-velocity zone.…”
Section: The History and Compositional Structure Of The Main Upper-mamentioning
confidence: 91%
“…This interpretation conforms with a number of other studies of the Baltic Shield (cf. Artemieva & Thybo 2008 for a recent review), including studies of xenoliths from Finland (Lehtonen et al 2004;Lehtonen & O'Brien 2009). The low P velocities and even lower S velocities and associated high V P /V S ratios west of the UMVB are consistent with a relatively thin, and hence warmer and less depleted lithosphere and a clear asthenosphere low-velocity zone.…”
Section: The History and Compositional Structure Of The Main Upper-mamentioning
confidence: 91%
“…In the present study, a caveat to this continuum model is that the proto-aillikite magma interacted with a lesser proportion of the same or similar metasomatized SCLM component that dominates the proposed source of the olivine lamproites, despite being separated by ∼100 km. In this regard, a geothermobarometric study of garnet and clinopyroxene xenocrysts from kimberlites and olivine lamproites ( Lehtonen & O'Brien, 2009 ), suggests that the lithospheric mantle beneath Kuusamo, is indeed similar to that beneath the Lentiira-Kuhmo cluster.…”
Section: Geodynamic and Source Constraints For ∼1200 Ma Olivine Lampr...mentioning
confidence: 99%
“…As an example of an area with a low level of anthropogenic seismic noise, we selected an area located in the Kuusamo Greenstone Belt (KuGB), Finland, because of numerous previous geological and geophysical studies there (Silvennoinen, 1991;Bruneton et al, 2004;Yliniemi et al, 2004;Silvennoinen and Kozlovskaya, 2007;Poli et al, 2012b;Pedersen et al, 2013;Silvennoinen et al, 2014;Tiira et al, 2014;Vinnik et al, 2014, etc.). Moreover, Weihed et al (2005) and Lehtonen and O'Brien (2009) have shown that this area is prospective for gold-and diamond deposits.…”
Section: Kuusamo Greenstone Belt Areamentioning
confidence: 99%
“…In our paper, we present details of this algorithm and illustrate its performance using passive seismic ambient noise data acquired in two areas of Fennoscandia: Pyhäsalmi mine (as an example of area with a high level of industrial noise) and the Kuusamo Greenstone Belt area (a quiet area prospective for new mining projects (Weihed et al, 2005;Lehtonen and O'Brien, 2009).…”
Section: Introductionmentioning
confidence: 99%